ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN PENDEKATAN RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, AND CAPITAL) STUDI PADA 4 BANK BUMN DI INDONESIA TAHUN 2019-2021 - Ginting, Nela Patricia; Damayanti, Damayanti; Destalia, Mediya (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine the soundness of 4 state-owned banks in 2019-2021 based on the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method. This type of research is descriptive research and the data collection method used in this research is the documentation method. The data analysis technique used in this research is the analysis of bank health by assessing the RGEC aspects, the Risk Profile factor through the NPL and LDR ratios, the Good Corporate Governance factor, the Earning factor through the ROA and NIM ratios, the Capital factor through the CAR ratio. The results show that in 2019-2021 bank health based on the Risk Profile aspect gets a healthy predicate, based on the GCG factor it gets a very good predicate, based on the Earnings aspect it gets a very healthy predicate, based on the Capital aspect it gets a very healthy predicate. the overall soundness of the bank in 2019-2021 received a very healthy predicate.